Komposisi dan Kelimpahan Makrozoobenthos Polychaeta di Pantai Maron dan Sungai Tapak Kel. Tugurejo Kec. Tugu Kota semarang - Mahfud, Mahfud; Widianingsih, Widianingsih; Hartati, Retno (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove area in Tugu District had been damaged because of function change as fishpond and agriculture. It because of fisherman shiplane, abaration and waste. Bad management area can change the invorenment and can be influence the ecosystem. As a concequence to the biota in that ecosystem include Polychaeta. The aim of research was finding out Compositions and Abundance of Macrozoobenthos Polychaeta in Maron Beach and Tapak River Tugurejo village Tugu District Semarang City. This research used descriptive exploratory method, determination of research area using purposive sampling method. Samples handling soaked in formalin 10% with rose Bengal. The result showed that it had been found 30 species include on 26 Polychaeta and 4 other worm (Allies). Abundance was ranged 2.126 ind./m2 and species with high abundance is Capitella (1.027 ind./m2), Terebellidae (375 ind./m2), Chaetopterus (300 ind./m2). Diversity index of all station were in low category (1,18-2), Uniformity index include in low category (0,40-0,72) and the Dominance index Station A (0,61).